PENGEMBANGAN MEDIA PEMBELAJARAN “MATE-MATRIKS” BERBASIS ANDROID MENGGUNAKAN SOFTWARE ADOBE ANIMATE CC - Muhammad Amin Ma’ruf; Nanang Nabhar Fakhri Auliya (CV. ADIBA AISHA AMIRA, 2025)
Interactive learning media is a solution that can increase students' interest and motivation in learning mathematics, especially in the discussion of matrices that are often considered difficult by students. The